A framework in analysing the strategies for governing innovation networks for public innovation. (4th March 2021) - Li, Yanwei
ABSTRACT: Innovation is essentially a collaborative initiative requiring the contribution of all involved actors. As no earlier framework has explicitly focused on the governance of collaborative networks for public innovation, a framework is needed to study how innovation networks contribute to making pubic governance more effective and innovative. This article constructs a conceptual framework consisting of six governance strategies, namely, participating, developing frameworks, managing interactions, sponsoring resources, establishing visions, and diplomacy. It can be applied to analyse specifically how innovation networks are governed to achieve effective innovation. Finally, the framework is discussed and research agendas are set.